2021
DOI: 10.15537/smj.2021.42.4.20200754
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of delirium in the critical care unit and risk factors in the Central Region, Saudi Arabia

Abstract: Objectives: To determine the incidence and risk factors of delirium in the cardiac care unit (CCU) and intensive care unit (ICU). Methods: This multicenter prospective observational study was conducted between July 2019 and November 2019 in the central region of Saudi Arabia. All patients admitted to the critical care units were enrolled, and their demographic data and risk factors of delirium were reported. Results: A total of 165 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The patients in our study were 49.1±17.3 years old on average, whereas mean age was 55±18 years in a study conducted by Abazid et al in 2021. 17 In our study, 66.7% patients were male which was similar to finding of Lobo et al ( 2021), who reported that male were 62.3% in total sample. 18 Our study found that the incidence of delirium was 33.3% after admission.…”
Section: Discussionsupporting
confidence: 91%
“…The patients in our study were 49.1±17.3 years old on average, whereas mean age was 55±18 years in a study conducted by Abazid et al in 2021. 17 In our study, 66.7% patients were male which was similar to finding of Lobo et al ( 2021), who reported that male were 62.3% in total sample. 18 Our study found that the incidence of delirium was 33.3% after admission.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding hypoalbuminemia, the relationship between malnutrition and delirium incidence and related outcomes is well documented. [22][23][24][25][26][27] However, while preoperative hypoalbuminemia as a measure of malnutrition is associated with postoperative delirium incidence, 20,[28][29][30][31] we could not locate evidence indicating that preoperative hypoalbuminemia predicts the disposition of postoperative patients who experience delirium.…”
Section: Discussionmentioning
confidence: 73%
“…Research and literature reviews have demonstrated patients in critical care units (CCUs) are at increased risk of delirium (Abazid et al., 2021; Ramos et al., 2023). Delirium is characterized by disturbance of consciousness and accompanying changes in condition.…”
mentioning
confidence: 99%